Evolutionary programming with gaussian and cauchy mutation technique optimal reactive power dispatch in load margin enhancement / Nik Mohd Alif Nik Idris - Nik Idris, Nik Mohd Alif (2013)
This report present evolutionary programming (EP) with Gaussian and Cauchy mutation technique in optimal reactive power dispatch (ORPD) in load margin enhancement. In this study, evolutionary programming is implemented in optimal reactive power dispatch in term of enhancement of load margin. The program will determine the voltage stability in the system. In this research, two types of mutation technique that is Gaussian and Cauchy mutation technique are implemented in evolutionary programming in order to. find the best technique to be adaptive in the system. In order to achieve the objective, the proposed technique are tested on IEEE 14, IEEE26, IEEE30 reliability test system (RTS) to ensure the reliability of the proposed technique.